Dampak Relokasi pada Pelaksanaan Pembangunan Resort dan Lapangan Golf bagi Komunitas Nelayan di Pulau Dompak, Provinsi Kepulauan Riau - Sari, Nika Purnama; Nisa, Khoirun; Evelin, Joana; Suryanti, Ulya Maylani; Sri Wahyuni (Dynamics of Rural Society Journal, 2024)
The government's plan to transform the Tanjung Siambang area into a tourist destination necessitates the relocation of fishermen's homes. Job diversification becomes a solution for fishermen in Tanjung Siambang to survive. Job diversification is a strategy that must be implemented by fishermen because, without it, they will face difficulties in meeting their household economic needs. Economic needs must be continually met to ensure daily life runs smoothly. The purpose of this study is to determine the impact of relocation due to the construction of resorts and golf courses on the fishing community in Dompak Island. This study uses a qualitative approach. This approach is used to describe the context of fishermen's lives in job diversification for survival. The data sources in this study are primary and secondary data obtained through observation and in-depth interviews. The results of the study show that many fishermen in Tanjung Siambang Village have diversified their jobs by working as laborers, members of the municipal police (Satpol PP), and gardening. Moreover, the roles of fishermen's wives also contribute to the economy to meet daily needs. The impact of the relocation due to development has led the community to choose side jobs to meet daily needs and create independence by starting home industries. The development of the golf course has caused the local community to lose their homes and made access to boats for fishermen more difficult. This has fostered the creativity of the local community, which is a novelty in this study.